Ultrafast longitudinal and transverse dielectric response of collective polar modes in liquids - Matthias Runge; Michael Woerner; Thomas Elsaesser (Physical Review Research, 2025)
Electrons solvated in polar liquids are a prototypical many-body system, in which electric interactions on different length scales have a strong impact on quantum states and elementary excitations. Impulsively excited polarons in liquid water and alcohols display coupled coherent motions of electrons and their solvation shells at terahertz (THz) frequencies, affecting both the longitudinal and transverse dielectric function. To address the barely characterized connection between the longitudinal and transverse dielectric response in experiment, an ultrafast pump-probe scheme is employed. Two femtosecond near-infrared pump pulses in sequence generate solvated electrons by ionization of isopropanol solvent molecules. The resulting changes of the dielectric function are mapped in time-resolved measurements by a broadband THz probe pulse, which is detected in a phase-resolved way. Longitudinal polaron oscillations modulate both the longitudinal and transverse dielectric function with a frequency set by the partial electron concentration generated in the separate excitation steps. On top, the transverse response includes steplike components, which are governed by the total electron concentration and well described by Clausius-Mossotti theory. The different longitudinal and transverse response is caused by the different character and spatial range of the underlying electric interactions.